2011
DOI: 10.1007/s00213-011-2509-8
|View full text |Cite
|
Sign up to set email alerts
|

Does minocycline, an antibiotic with inhibitory effects on microglial activation, sharpen a sense of trust in social interaction?

Abstract: These results suggest that minocycline led to more rational decision-making strategies, possibly by increasing emotion regulation. Since minocycline is a well-known inhibitor of microglial activation, our findings may open a new optional pathway for treating mental states in which a component of rational decision making is impaired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 36 publications
5
20
0
Order By: Relevance
“…However, estrogens act on many different ways in the brain and may cause their effect by mechanisms unrelated to inflammation, eg, by affecting angiotensin and dopamine neurotransmission. 75,76 Minocycline is a strong inhibitor of microglia cell activation 24 and may, therefore, be expected to have potent effects on symptom severity. This component was provided in a relatively high dose of 200 mg for a relatively long time (4-12 mo), including 2 studies that restricted inclusion to FEP patients, but the results in these 348 patients were not significant although heterogeneity was high.…”
Section: E Sommer Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…However, estrogens act on many different ways in the brain and may cause their effect by mechanisms unrelated to inflammation, eg, by affecting angiotensin and dopamine neurotransmission. 75,76 Minocycline is a strong inhibitor of microglia cell activation 24 and may, therefore, be expected to have potent effects on symptom severity. This component was provided in a relatively high dose of 200 mg for a relatively long time (4-12 mo), including 2 studies that restricted inclusion to FEP patients, but the results in these 348 patients were not significant although heterogeneity was high.…”
Section: E Sommer Et Almentioning
confidence: 99%
“…24 Three studies assessed the effect of minocycline addition to antipsychotic treatment. All studies used a relatively high dose of 200 mg and long duration of treatment, ranging from 4 to 12 months.…”
Section: Minocyclinementioning
confidence: 99%
“…Healthy Japanese adult males made a monetary decision about whether or not to trust an anonymous partner after a 4-day oral administration of minocycline. Our first trial revealed that the minocycline group showed a positive correlation between their monetary score in trust game and their evaluation scores of others’ trustworthiness in a questionnaire (Yamagishi’s General Trust Scale), but surprisingly the placebo group did not (60). It would be rational to consider the monetary and questionnaire score to be positively correlated because both scores measure the other’s trustworthiness, but there was no positive correlation with the placebo group.…”
Section: Possible Glial Roles In Human Mental Functionsmentioning
confidence: 96%
“…Interestingly, we have recently reported that minocycline modulates human social decision-making in healthy volunteers [186,187]. Therefore, minocycline may effect not only on psychiatric patients but also on healthy persons.…”
Section: Minocyclinementioning
confidence: 98%